2014
DOI: 10.1353/hpu.2014.0106
|View full text |Cite
|
Sign up to set email alerts
|

Low Socioeconomic Status is Associated with Increased Risk for Hypoglycemia in Diabetes Patients: The Diabetes Study of Northern California (DISTANCE)

Abstract: Background Social risk factors for hypoglycemia are not well understood. Methods Cross-sectional analysis from the DISTANCE study, a multi-language, ethnically-stratified random sample of adults in the Kaiser Permanente Northern California diabetes registry, conducted in 2005-2006 (response rate 62%). Exposures were income and educational attainment; outcome was patient report of severe hypoglycemia. To test the association, we used multivariable logistic regression to adjust for demographic and clinical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
(48 reference statements)
4
30
1
1
Order By: Relevance
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…American Indians were found to be at increased risk for hypoglycemia in the one study that analyzed this group separately. Two of the four studies that included Asians demonstrated them to be at increased risk compared to whites, with OR 1.28 (95 % CI 1.09-1.51) for report of hypoglycemia [37] and OR 1.15 (95 % CI 1.03-1.75) for acute hypoglycemia admissions [19]. One study found this group to be at decreased risk for diabetes agents-related ADEs, with 37.3 % of Asian participants reporting ever experiencing hypoglycemia, while over 50 % of the other racial or ethnic groups reported this outcome [40].…”
Section: Diabetes Agents-related Adverse Drug Eventsmentioning
confidence: 99%
“…In the DISTANCE Study, ~11% of surveyed diabetes patients reported an SH event in the previous 12 months, while only ~0.5% of that cohort received an ED or inpatient diagnosis of SH. (Sarkar et al, 2010) Since it is unclear what factors led persons experiencing an SH event to receive medical attention in the ED or hospital, racial/ethnic patterns of self-reported SH(Berkowitz et al, 2014; Lipska, et al, 2013) may differ from SH diagnosed at a medical facility. Moreover, since we based findings on SH identified via primary or principal diagnoses, findings cannot be generalized to SH events that were secondary to other diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…[18] A limited number of studies have investigated the associations of these conditions with the influence of self-management variables and socioeconomic status. [9,19,20] Therefore, we investigated whether diabetes self-management, education, socioeconomic status, and known risk factors for severe hypoglycemia were associated with HMA compared to NSH. We also determined the predictors of severe hypoglycemia with neurological sequelae.…”
Section: Introductionmentioning
confidence: 99%